Safety of switching from brand-name to generic levetiracetam in patients with epilepsy - Bosak M; Słowik A; Turaj W (Dove Medical Press, 2017)
Magdalena Bosak, Agnieszka Słowik, Wojciech Turaj Department of Neurology, Jagiellonian University Medical College, Kraków, Poland Purpose: The approach to the use of generic antiepileptic drugs has recently evolved from major concern to general acceptance, but the evidence related specifically to the safety of switching from brand-name to generic levetiracetam (LEV) is scarce. The aim of the study was to assess the risk of increased frequency of seizures or other adverse events after replacement of a brand-name LEV with a generic one.Patients and methods: This retrospective analysis included 159 patients treated with LEV in a tertiary outpatient epilepsy clinic. We included all patients diagnosed with epilepsy who were treated with LEV as at March 1, 2013. Most patients were forced to switch to the generic LEV because of the sudden rise in cost of the branded LEV. We recorded data on age, sex, age at onset of epilepsy, type of epilepsy, and its treatment. We analyzed data from one visit before potential switching and from two visits after the potential switching. The interval between visits was typically 3 months. We registered an increase in the frequency of seizures and in the occurrence of adverse events.Results: Among 151 subjects who switched to generic LEV after March 1, 2013, increased frequency of seizures was noted in 9 patients (6%) during the first follow-up visit. Patients with increased frequency of seizures did not differ from other patients regarding sex, age, age at the onset of epilepsy, and the median dose of LEV before switching or the median duration of treatment with LEV before switching. Two patients returned to brand-name LEV. Adverse events were noted in six other patients (4%) and included somnolence, irritability, or dizziness.Conclusion: Switching from brand-name to generic LEV is generally safe. Keywords: levetiracetam, generic, branded, epilepsy, switching, adverse event